The Knowledge of Supervision Effect’s Toward Accountability of Junior High School Headmaster - Elfisa, Yesi; Saukani, Saukani (PPSDP International Journal of Education, 2023)
This study aimed to assess the direct effect between the variable of knowledge of supervision toward accountability of Junior High School headmaster in Jambi Province. This research was a quantitative study using a survey method conducted against the headmaster of Junior High School. The sampling technique using the simple random sampling with a population of 550 and 123 samples. In this research found that the significant difference between knowledge of supervision toward the headmaster accountability of Junior High School amounted to 17.012. then, this study was useful for government and the headmaster of Junior High School in Muaro Bungo, Sarolangun and Kota Jambi region. and the novelty of this study was the knowledge of supervision is the main concept should be mastered by headmaster to be accountable.